1992
DOI: 10.1152/jappl.1992.73.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of spontaneous and evoked motility in the isolated perfused porcine duodenum

Abstract: The aims of the study were to evaluate characteristics of spontaneous motility and of the ascending excitatory peristaltic reflex (AEPR) and intraluminal cross-sectional area in the isolated perfused porcine duodenum. The parameters were measured by an intraluminal catheter by use of the perfused side-hole technique and impedance planimetry. Respiratory parameters such as pH and oxygen consumption and the arterial perfusion pressure were monitored and did not vary significantly throughout the study time. Spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Furthermore, the pharmacological data showed that spontaneous and secondary motility was neurogenic and mediated via muscarinic receptors. The pharmacological data are consistent with previous findings in the porcine duodenum [22]. Since TTX did not further enhance motility, no neurogenic tonic inhibition of smooth muscle in the investigated segments was present.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the pharmacological data showed that spontaneous and secondary motility was neurogenic and mediated via muscarinic receptors. The pharmacological data are consistent with previous findings in the porcine duodenum [22]. Since TTX did not further enhance motility, no neurogenic tonic inhibition of smooth muscle in the investigated segments was present.…”
Section: Discussionsupporting
confidence: 91%
“…The reduced afferent firing found in the present study in the obstructed segments may relate to the abovementioned changes. The change in nerve and ganglia morphology and function will also have an impact on smooth muscle contractile activity due to intrinsic stretch sensitive neural reflexes (18). During distension we and others found increased muscle force and hyposensitivity to stretch (36).…”
Section: Afferent Discharge In Hypertrophic Intestinementioning
confidence: 62%
“…This makes it difficult to apply the acquired information to an intact segment [11]. The compliance and tension-strain relations in thin-walled plane strain models were obtained from measurements of pressure and CSA in the normal and diseased esophagus using impedance planimetry [12][13][14][15][16][17][18]. However, both compliance and the tension-strain relation neglect the wall thickness.…”
Section: Introductionmentioning
confidence: 99%